BUSINESS AND EXPORT DEVELOPMENT ORGANIZATION SEBAGAI FASILITATOR DALAM PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH DI TABANAN - Ardyastia, I Putu Angga; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
The implementation of MSME empowerment focuses on empowering MSMEs in Tabanan. This study uses qualitative data as the main data and numbers as additional data in descriptive-explanative research. This study examines the efforts to empower MSMEs which are analyzed by empowering Jim Ife. The results of this research are SMEs Pudak Wangi, Padma Herbal, Lovey Bali, Balinese Hindu Mosaic, Tabanan Mushroom, Mamasugi Bali and social observers say that from the start they have had local potential both in resources, culture, skills, processes, knowledge, including working in solidarity. Obstacles such as production, raw materials, capital, marketing, miscommunication regarding the type of coaching carried out, coaching that is not well targeted and the pandemic forced the offline coaching program to be cashed out. It is hoped that BEDO can prioritize listening to the problems and needs of the assisted SMEs before making programs. Keywords: SMEs, BEDO, Empowerment, Tabanan